Role Plays to Enhance Readiness for Practicum: Perceptions of Graduate & Undergraduate Social Work Students. (2nd October 2022) - Allemang, Brooke; Dimitropoulos, Gina; Collins, Tara; Gill, Priyanka; Fulton, Amy; McLaughlin, Anne-Marie; Ayala, Jessica; Blaug, Carrie; Judge-Stasiak, Angela; Letkemann, Lorraine
ABSTRACT: Although field education is considered the signature pedagogy of social work education, there is a paucity of research examining how Bachelors of Social Work (BSW) and foundation year-Masters of Social Work (FY-MSW) students perceive strategies designed to prepare them for field placement. To enhance readiness for practicum, an interactive role play activity was introduced to BSW and FY-MSW students, and their perspectives of the activity were elicited using focus groups. A thematic analysis of the transcripts resulted in five themes: enhanced perspective-taking, "we have a voice", reflections on supervisory relationship, pressure to excel in student role, and opportunity to practice in a safe space. The findings provide guidance for implementing pre-practicum activities appropriate to students' level of education and training.